Tylopilus jiangxiensis, a new species of Tylopilus s. str. from China - Zhao, Kuan; Zhang, Fu-Mao; Zeng, Qing-Qing; Han, Li-Hong; Li, Yan-Chun (Phytotaxa, 2020)
Tylopilus jiangxiensis is described as a new species characterized by its small basidiomata, yellowish brown pileal and stipe surface, pallid to pinkish hymenophore, smooth stipe surface and white context without color change when bruised. Molecular phylogenetic analyses based on five gene makers (ITS, nrLSU, tef1-α, rpb1 and rpb2) confirmed it as a novel member of the genus Tylopilus s. str. Its morphological descriptions and illustrations are provided.